Delineasi Zona Prospek Sistem Panasbumi Daerah ‘P’ Menggunakan Pemodelan Multi Dimensi Data Magnetotelurik Terintegrasi Data Geologi dan Geokimia - Puji Suharmanto; Yunus Daud; ahmad zarkasyi (LPPM, 2018)
A study for delineating geothermal system of prospect area “P” has been done by using multi-dimensional modeling of magnetotelluric data. Physiographycally, geothermal prospect of “P” area is located at non-volcanic Banda inner arc hosted by Malihan Sekis rock complex with Perm-Trias age. The existance of geothermal system in this area is indicated by the presence of thermal manifestations in form of 6 chloride-bicarbonate hot springs with temperature in the the range of 37-67oC, and pH of 6-7. The development of geothermal system is most probably associated with strong tectonic activity caused by the collision between Seram island plate and Australian plate that ignite the occurence of intrussive body as heat source. In order to know the subsurface information of prospect area, magnetotelluric (MT) survey has been done. The processing of MT data was started from time-series data, continued by noise filtering, rotation of strike orientation and static shift correction to obtain better MT curve. The data were then being inversed by means of 1-Dimensional, 2-Dimensional and 3-Dimensional inversion methods. Reservoir temperature is estimated to be around 160-180 oC and classified as moderate temperature. The result of MT data inversions shows the presence of conductive layer (<15 ?m) with 500-1000 m thickness that is interpreted as clay cap og geothermal system. High resistivity zone (>300 ?m) with updome shape appears underneath the manifestations occurence (MAP1, MAP2, MAP4, and MAP5), indicating that the heat source is located in northern part and elongate to souteast direction. The conceptual model of geothermal system was built based on integrated interpretation of geological, geochemical and geophysical data. The prospect area and recommendation of drilling location is estimated to be ± 3 km2 around upflow zone.Keywords: Prospect zone, geothermal system, magnetotelluric method, multi-dimension modeling